The Indian Judiciary's Role in Enforcing Justice through Public Interest Litigation. (International Journal of Food and Nutritional Sciences, 2022)
Public Interest Litigation (PIL) stands as a cornerstone in the legal landscape of India, designed to empower the underprivileged and address societal issues. This paper critically examines the trajectory of PIL, tracing its evolution from a mechanism of justice to a focal point of judicial activism. Focusing on the judiciary's pivotal role, it explores the challenges faced by PIL in recent times and evaluates the impact of judicial overreach. PIL's genesis lies in the principles of judicial review, aiming to provide a legal avenue for the marginalized who face barriers in accessing justice. However, the paper scrutinizes the contemporary application of PIL, revealing instances of misuse and over-enthusiastic interventions by the judiciary. The phenomenon of judicial activism, particularly in the context of PIL, is dissected, emphasizing the blurred lines between correcting government actions and inadvertent encroachments into the executive and legislative domains. Drawing on specific PIL cases, ranging from environmental concerns to intricate engineering projects, the paper illuminates the unintended consequences of judicial activism. It underscores the need for substantial reforms to realign PIL with its original intent while preserving its potency as an instrument for justice. Instances where the judiciary has assumed roles better suited for other branches of government are analysed, raising questions about the delicate equilibrium essential for a functional democracy. Overall, the paper advocates for a nuanced understanding of the judiciary's role in PIL. While acknowledging the importance of safeguarding individual rights and ensuring justice, it emphasizes the necessity for the judiciary to exercise restraint and adhere to the core principles of judicial review. By striking a balance between activism and restraint, the judiciary can fortify PIL as an effective tool for justice without compromising its foundational principles or contributing to unintended consequences.